Peutz-Jeghers syndrome without mucocutaneous pigmentation: a case report - Mozaffar, Mohammad (Research Institute for Gastroenterology and Liver Diseases, 2012)
Peutz–Jeghers syndrome is a rare condition characterized by mucocutaneous pigmentation, polyposis and an increased cancer risk at a number of gastrointestinal and extra intestinal organs. We present a patient with a history of gastrointestinal bleeding with no mucocutaneous pigmentation. Upper and lower gastrointestinal endoscopy revealed multiple polyps located in the deuodenum and colon. Histopathological evaluation of the polyps revealed hamartomatous polyps of Peutz-Jeghers syndrome.